-3p+4=4x-3(x+2)

Simple and best practice solution for -3p+4=4x-3(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3p+4=4x-3(x+2) equation:


Simplifying
-3p + 4 = 4x + -3(x + 2)

Reorder the terms:
4 + -3p = 4x + -3(x + 2)

Reorder the terms:
4 + -3p = 4x + -3(2 + x)
4 + -3p = 4x + (2 * -3 + x * -3)
4 + -3p = 4x + (-6 + -3x)

Reorder the terms:
4 + -3p = -6 + 4x + -3x

Combine like terms: 4x + -3x = 1x
4 + -3p = -6 + 1x

Solving
4 + -3p = -6 + 1x

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -3p = -6 + -4 + 1x

Combine like terms: 4 + -4 = 0
0 + -3p = -6 + -4 + 1x
-3p = -6 + -4 + 1x

Combine like terms: -6 + -4 = -10
-3p = -10 + 1x

Divide each side by '-3'.
p = 3.333333333 + -0.3333333333x

Simplifying
p = 3.333333333 + -0.3333333333x

See similar equations:

| x^2+2x+19=0 | | 4r+2+5r-12=15 | | x^2-3x+6x-18=0 | | 4x-25=4(x+3) | | 0.2x^3+0.5x^3-0.4x^3=0 | | 25w^2+30w+9=0 | | -8y+3(y-5)=-5(y+3) | | 4(3x-5)+7=2(6x+7) | | 5y-9+y+37=6y+30-2y | | -5x^2+4+18=0 | | 12x^2+8=104 | | -5x-7=-7x+13 | | 10y-3=7 | | -8x-11x=133 | | q-5=35 | | 4+4m=-m-1 | | 12x^2=6-x | | -5.5x=110.0 | | 3=-3x | | (4x^4+2n)-(8x^4+14n)= | | -5.5=110.0 | | -(3x-2)=3x | | 5z^6-(-3z^6-3v)= | | 6x+4y+xy+24= | | (-2w^4+11v)-(-15w^4)= | | -23+x=x+15 | | 3+2(2x-3)=1 | | 8x^9-(6x^9-7)= | | Y-6(y-4)=(-8y+15)-5 | | (-9b^9-11n)-(6b^9-7n)= | | 2x-12=6x-2 | | 15x^2=16x+7 |

Equations solver categories